2006
DOI: 10.1159/000094226
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of preimplantation embryos diagnosed with monosomy by fluorescence in situ hybridization (FISH)

Abstract: This report is a retrospective study of preimplantation embryos diagnosed with monosomy for chromosomes 13, 15, 16, 18, 21, 22, X and Y on day 3 to determine the rate of true positives, false positives and/or mosaicism and to assess if these embryos are suitable for in vitro fertilization (IVF) transfer. In a one year period, 80 patients went through preimplantation genetic diagnosis for aneuploidy screening (PGD-AS). Monosomy was diagnosed in 51 embryos. Fluorescence in situ hybridization (FISH) was then perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
1
5
0
1
Order By: Relevance
“…Using an SNP array for clinically discarded embryos, we found that whole chromosome loss is the most frequently occurring abnormal event, consistent with a previous report 42 . In addition, whole chromosome gain and segmental deletions were also frequently observed as previously reported 43 44 45 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using an SNP array for clinically discarded embryos, we found that whole chromosome loss is the most frequently occurring abnormal event, consistent with a previous report 42 . In addition, whole chromosome gain and segmental deletions were also frequently observed as previously reported 43 44 45 .…”
Section: Discussionsupporting
confidence: 91%
“…Following the use of SNP array-based 24 chromosome aneuploidy screening, two out of 3,401 blastocysts demonstrated isodisomy in human 2PN-derived blastocysts after trophoblast cell biopsy, with an associated frequency of UPD of 0.06% 42 . In our previous study, the percentage of UPD in human clinically discarded blastocysts was 3.7% 46 , consistent with data generated as part of the present study (2.7%).…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference was found in our research between monosomy and trisomy rate. The cause for that difference might be technical elements (FISH interpretations) but it may also suggest that chromosome loss is more common in aneuploid embryo [9].…”
Section: Chromosomal Imbalances In Embryosmentioning
confidence: 99%
“…Munne et al (27) in 1997 reported that IVF culture conditions and/or hormone stimulation protocols may induce chromosomal mosaicism. More recently, mosaicism has been found in 16% to 67% of embryos after preimplantation genetic diagnosis (PGD) in couples requiring ART (28,29). Because, in many cases, preimplantation genetic diagnosis is conducted in patients with infertility and potential mosaics are not transferred, there is no available cytogenetic followup evaluation to determine the actual prevalence and consequence of these mosaics.…”
mentioning
confidence: 99%